Bridging the gap between brand gender and brand loyalty on social media: exploring the mediating effects - Carvalho, Leonor Vacas de (2020)
Brand gender has been suggested to influence consumer’s responses to the brand. The aim of this research was to deepen the understanding of the relationship between brand gender and brand loyalty by developing a research model to test the relationships among brand gender, active consumer engagement with the brand on social media, perceived quality, brand love and brand loyalty. The hypotheses were tested using structural equation modelling. The results support the importance of active consumer brand-engagement, perceived quality and brand love in underpinning the underlying process between brand gender and brand loyalty. Hence, this research complements prior work on brand gender and confirms the important benefits of a clear brand gender positioning by showing that a strong gender identity will enhance loyalty towards the brand.